Integration of Intraoperative Neurophysiological Monitoring into Laparoscopic Pelvic Nerve Decompression Surgery: A Novel Technique for Protecting Pelvic Nerves - Elif Cansu Gundogdu; Ahmet Kale; Metin Mercan; Vildan Yayla; Ugur Efe Ozcan; Taner Usta; Esra Keles (IMR Press, 2023)
Background: This study aims to present a novel technique that integrates intraoperative neurophysiological monitoring (IONM) into laparoscopy for continuous monitoring of pelvic nerves at risk during surgery to ensure their protection. Methods: This is a prospective analysis of 10 consecutive patients receiving surgical treatment for proven diagnosis of lumbosacral plexus nerve entrapment. Patients with symptoms of chronic pelvic pain, dyspareunia, dysmenorrhea, and severe, burning sharp pain on the lower extremity dermatomes were included. Laparoscopic decompression of lumbosacral plexus nerve entrapment with intraoperative neuromonitoring was performed between January 2021 and February 2022. Intraoperative neuromonitoring records (spontaneous electromyography (EMG), free-run EMG recordings, transcranial electrical motor-evoked potentials (TcMEP) recordings, direct nerve root stimulation recordings, and compound muscle action potentials (CMAPs) recordings) and preoperative and postoperative pain symptoms at one month were analyzed. Results: The median age of the patients was 29 (25-44) years. Neurovascular conflict, fibrosis, and abnormal piriformis muscle were identified as the three main etiologies of nerve entrapments. There were no statistically significant differences in transcranial motor evoked potential responses on the operated extremity side before and after decompression surgery or in the amplitude difference changes of TcMEP responses between the operated and non-operated extremity sides (p > 0.05). Dyspareunia visual analogue scale (VAS) scores showed a significant decrease at the first month postoperatively (p-value = 0.027). Conclusions: Integrating intraoperative neurophysiological monitoring into laparoscopy facilitates the monitoring of the patient's motor function and prevents both permanent and transient nerve damage during pelvic nerve decompression surgery. This technique holds promise in enhancing surgical safety and preserving pelvic nerve function. The study was registered at https://clinicaltrials.gov (registration number NCT06009640).